RSC96 Schwann Cell Proliferation and Survival Induced by Dilong through PI3K/Akt Signaling Mediated by IGF-I. (8th June 2011) - Chang, Yung-Ming; Kuo, Wu-Hsien; Lai, Tung-Yuan; Shih, Ying-Ting; Tsai, Fuu-Jen; Tsai, Chang-Hai; Shu, Wen-Tong; Chen, Ying-Yu; Chen, Yueh-Sheng; Kuo, Wei-Wen; Huang, Chih-Yang
Abstract : Schwann cell proliferation is critical for the regeneration of injured nerves. Dilongs are widely used in Chinese herbal medicine to remove stasis and stimulate wound-healing functions. Exactly how this Chinese herbal medicine promotes tissue survival remains unclear. The aim of the present study was to investigate the molecular mechanisms by which Dilong promote neuron regeneration. Our results show that treatment with extract of Dilong induces the phosphorylation of the insulin-like growth factor-I (IGF-I)-mediated phosphatidylinositol 3-kinase/serine-threonine kinase (PI3K/Akt) pathway, and activates protein expression of cell nuclear antigen (PCNA) in a time-dependent manner. Cell cycle analysis showed that G1 transits into the S phase in 12–16 h, and S transits into the G2 phase 20 h after exposure to earthworm extract. Strong expression of cyclin D1, cyclin E and cyclin A occurs in a time-dependent manner. Small interfering RNA (siRNA)-mediated knockdown of PI3K significantly reduced PI3K protein expression levels, resulting in Bcl2 survival factor reduction and a marked blockage of G1 to S transition in proliferating cells. These results demonstrate that Dilong promotes the proliferation and survival of RSC96 cells via IGF-I signaling. The mechanism is mainly dependent on the PI3K protein.